Angry bowels breaking hearts: a case series. Issue 5 (3rd September 2018) - Soliman, Youssef; Soliman, Megan; Ahmad, Qamar; vonDoenhoff, Laura
ABSTRACT: Stress cardiomyopathy or Takotsubo cardiomyopathy (TCM) is transient left ventricular apical akinesis in the absence of angiographic evidence of corresponding obstructive coronary artery disease. A classic presentation is of chest pain following intense emotional or physical stress. Reports of stress-inducing triggers include acute respiratory failure, sudden death of a loved one, sympathomimetic drugs, pheochromocytoma crisis, diabetic ketoacidosis, and even earthquakes. We report three cases of intra-abdominal etiologies precipitating Takotsubo cardiomyopathy: two with small bowel obstruction, and one with Clostridium difficile colitis.